2008
DOI: 10.1177/0149206307312511
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at Trust Between Managers and Subordinates: Understanding the Effects of Both Trusting and Being Trusted on Subordinate Outcomes

Abstract: Despite previous calls to examine trust from the perspectives of both the manager and subordinate, most studies have exclusively focused on trust in the manager. The authors propose that trust in the subordinate has unique consequences beyond trust in the manager. Furthermore, they propose joint effects of trust such that subordinate behavior and intentions are most favorable when there is high mutual trust. Findings reveal unique relationships of trust in manager and trust in subordinate on performance, organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
288
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(300 citation statements)
references
References 58 publications
4
288
2
1
Order By: Relevance
“…When asked what played an important role in his doctoral journey, he answered "Maybe also trust …Well, this was maybe unconscious but having someone who tells you 'I appreciate working with you and I would be happy to do a PhD with you', it also played a role". This is in line with theories about self-fulfilling and the Pygmalion effect, which suggest that one's expectations about a person can eventually lead one to behave in accordance with these expectations, and that person to behave and achieve in ways that confirm those expectations (Brower et al, 2009;Van Maele & Van Houtte, 2011).…”
Section: Trust As a Seedbed For Supportsupporting
confidence: 87%
See 1 more Smart Citation
“…When asked what played an important role in his doctoral journey, he answered "Maybe also trust …Well, this was maybe unconscious but having someone who tells you 'I appreciate working with you and I would be happy to do a PhD with you', it also played a role". This is in line with theories about self-fulfilling and the Pygmalion effect, which suggest that one's expectations about a person can eventually lead one to behave in accordance with these expectations, and that person to behave and achieve in ways that confirm those expectations (Brower et al, 2009;Van Maele & Van Houtte, 2011).…”
Section: Trust As a Seedbed For Supportsupporting
confidence: 87%
“…In educational literature, recent studies have highlighted the positive role of teachers' trust in their students for the students' achievement (Goddard, Tschannen-Moran, & Hoy, 2001;Meirieu, 2008;Van Maele & Van Houtte, 2011;Watson & Ecken, 2003). In organizational psychology, research has stressed the importance of managers' trust in their subordinates for persistence and productivity in individuals and organizations (Brower, Lester, Korsgaard, & Dineen, 2009;Colquitt, Scott, & LePine, 2007).…”
Section: Trust As a Seedbed For Supportmentioning
confidence: 99%
“…The successful results of psychological empowerment require raising the level of trust between the employee and the supervisor, as well as between staff and top management. When subordinate trusts the supervisor, that leads to improved performance of the work and contribute to the improvement of organizational citizenship behavior, and encourages subordinate to maintain the relationship and stay with the organization (Colquitt et al, 2007;Brower et al, 2009); and the employee creates value for the organization through the extra efforts of subordinates (Mayer & Gavin, 2005). Tan and Tan (2000) confirmed that there is a positive relationship between trust in the supervisor and factors of ability, integrity and charity.…”
Section: Trust In Supervisorsmentioning
confidence: 99%
“…Tan and Tan (2000) confirmed that there is a positive relationship between trust in the supervisor and factors of ability, integrity and charity. Moreover, when there is an environment based on trust, it can lead to a sense of responsibility among the subordinates (Cropanzano & Mitchell, 2005) and improvement on their commitment (Brower et al, 2009). In addition, individuals who receive support from their direct supervisor will have greater sense of self-efficiency, which in turn supports a sense of their ability to influence and be independent (Spreitzer, 1996).…”
Section: Trust In Supervisorsmentioning
confidence: 99%
“…Obtaining the desired results of psychological empowerment requires raising the level of trust between employee and supervisor, and between staff and top management. Subordinates that trust their supervisor results in improved work performance, boosts organizational citizenship, and encourages subordinates to remain with the organization (Brower et al, 2009;Colquitt et al, 2007). In such cases, the employee makes extra efforts to create value for the organization (Mayer and Gavin, 2005).…”
Section: Trustmentioning
confidence: 99%